Analysis of the Influence of Natural Bathing Tourism Destinations on Village MSME Income Rumah Galuh Kabupaten Langkat - Julia Fitri; Ahmad Fadlan (MultiTech Publisher, 2024)
Tourism generates demand for goods and services, leading to various industries such as craft, consumer products, service, and restaurants. Langkat Regency, particularly in Sei Bingai District, has numerous tourist attractions, including Pelaruga natural baths and seven angels in Rumah Galuh Village. However, these attractions face obstacles such as lacking a Base Transceiver Station (BTS), public toilets, visitor huts, and promotions. Additionally, infrastructure such as roads, electricity networks, clean water, and communications networks is lacking. This research aims to analyze capital factors, business location, type of merchandise, selling price, promotion, infrastructure, and number of visitors relevant to the income of MSMEs in Rumah Galuh Village, Langkat Regency. Confirmatory factor analysis (CFA) is used to analyze data. Results show that facilities and infrastructure, number of visitors, promotion, and capital have a significant effect on MSMEs' income in Rumah Galuh Village, while business location, type of goods, and selling price have a negative effect. The results of simultaneous hypothesis testing show that facilities and infrastructure, number of visitors, promotion, and capital together have a positive and significant effect on MSMEs' income in Rumah Galuh Village